2015
DOI: 10.1007/s10901-015-9457-2
|View full text |Cite
|
Sign up to set email alerts
|

Municipal land allocations: integrating planning and selection of developers while transferring public land for housing in Sweden

Abstract: An essential component in all housing developments is suitable land. Besides being buildable, this implies land approved for housing in a marketable and consequently implementable location. Insufficient supply of suitable land to housing developers could affect the supply of housing. In Sweden, a lot of land appropriate for housing is owned-often since many years back-by municipalities and supplied to developers through the use of 'land allocations'. A land allocation connects a developer and a municipality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…a marketable housing project). After, and if, a development right has been regulatory determined in the land use plan, the land is transferred from the municipality to the developer who carries out the implementation (Caesar, 2016). 5 While the list of predefined conditions made by the municipality prior to the negotiation can be extensive as well as very basic it typically includes the tenure.…”
Section: Municipal Landownership and Land Allocationmentioning
confidence: 99%
“…a marketable housing project). After, and if, a development right has been regulatory determined in the land use plan, the land is transferred from the municipality to the developer who carries out the implementation (Caesar, 2016). 5 While the list of predefined conditions made by the municipality prior to the negotiation can be extensive as well as very basic it typically includes the tenure.…”
Section: Municipal Landownership and Land Allocationmentioning
confidence: 99%
“…The public authority can influence the conditions for competition within the property markets via the selection of building developers. However, this control is not without problems since the decisions may have low transparency (Caesar, 2016).…”
Section: Additional Public Control Via Public Land Developmentmentioning
confidence: 99%
“…Needham, 1992) and Sweden (see e.g. Caesar, 2016). While in these three countries public land development has been the dominant development strategy for long, land development strategies led by private sector can be (and are) used as well.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, municipalities own land suitable for housing projects (Boverket 2013), which can be sold to developers by imposing specific requirements to finalise the sale (SFS 2014:899; Caesar 2016), a process similar to the method used in procurement activities, Figure 1 (Weele 2010;Sanderson et al 2015). Further, Caesar (2016) found that the land allocation activity could in its current form result in barriers for small or financially weak developers, excluding them as a result of an insufficient structure in the land allocation process combined with subjective decisionmaking by municipalities (Caesar 2016). This could be avoided by adopting a process similar to a procurement model, which provides structure and transparency for all involved parties (Weele 2010;Sanderson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although land allocation processes play a dominant role in housing supply, Caesar (2016) concluded that research about land allocation hardly exists. However, Caesar's (2016) research related to land allocation is established on a model by Kalbro (2000), which identifies a method to classify the building development process by Swedish municipalities based on developers' involvement in municipalities' plan preparation. Caesar (2016) developed a model to synchronise the steps between the land allocation-and planning processes to provide an understanding of the involved activities up to project implementation.…”
Section: Introductionmentioning
confidence: 99%